Development and evaluation of food environment audit instrument: AUDITNOVA - Camila Aparecida Borges; Patricia Constante Jaime
ABSTRACT OBJECTIVE To develop and assess the reliability of an instrument that enables auditing information on consumer food environment indicators, such as availability, price, promotional and advertising strategies, and quantity of brands available, using the food recommendations adopted by the Dietary Guidelines for the Brazilian Population as a theoretical basis. METHODS This is a methodological study in two phases: 1. development of the audit instrument and 2. assessment of its reliability and reproducibility . The Content Validity Index was estimated for each instrument item (>0.80 satisfactory). Inter-rater and test-retest reliability were assessed by percentage agreement and Kappa coefficients. Pearson's correlation coefficient and Scatter-plots were used to measure the degree of linear correlation between two quantitative variables. RESULTS The Content Validity Index was 0.91. Inter-rater and test-retest reliability were mostly high (Kappa> 0.80), for food availability indicators. Among the items that measure advertising, Kappa values for inter-rater reliability ranged from 0.57 to 1.00 and for the test-retest ranged from 0.18 to 0.90. Prices and quantity of brands showed a positive linear correlation between measurements performed by researcher 1 and 2 and between visits 1 and 2. CONCLUSIONS AUDITNOVA is reliable for measuring aspects such as availability, price, quantity of brands, and advertising of foods available in the consumer food environment.